Photography as a Social Research Method - Langmann, Sten (Springer Singapore, 2018)
This book focuses on photography within the social research field, building a solid foundation for photography as a social research method and describing different techniques and applications of photo research. It provides a comprehensive approach to research photography, from preparation and the ethical considerations that need to be understood prior to going into the field, to collecting data, analysis and preparing research for publication. It also introduces artistic genres of photography to help readers with the choices they make when pursuing photographic research and as a reminder that when collecting photographs that they are in fact producing art. The ethical issues examined place a new focus on dignity and considerations of participant anonymity and recognition, informed consent, working with vulnerable groups, unequal power relationships and possible intervention. Combining preparation and ethics, it examines how best to collect and take good photographs, and explores the practical issues of stigma and introduces Verstaendnis (german: understanding) to aid researchers in the field. Subsequently, the book discusses the different photo-analytical approaches for researchers and provides examples of how to analyse photographs using the different techniques. Lastly, it offers guidelines, with examples, for researchers wanting to publish their work.